Exposing Commodification Practices in TVOne's Talk Show X Production Related to Issues the Murder of Brigadier Yosua Hutabarat (Vincent Mosco's Approach) - Dwi Anggia Ritmadhini; Aryo Subarkah Eddyono (Profetik: Jurnal Komunikasi, 2024)
The political economy in the TV industry forces a TV company to take various steps to sustain its business. This also happens in TVOne, particularly in the production of talk show X, where the commodification of content, viewers, and workers occurs. This study aims to explore the economic and political practices within the production process of talk show X, from the commodification of content, audience, and workers, particularly related to the murder of Brigadier Yosua Hutabarat. This is qualitative research that is conducted using a critical paradigm. The data were collected through in-depth interviews, observation, and document studies linked to Vincent Mosco’s theory. The results show that the content and audience data of Talk Show X are turned (turns) into commodities that have valued and generated profits for media companies, also, the worker commodification occurred against Talk Show X stakeholders. This research is limited to the economic and political practices within the production of talk show X, focusing on the murder of Brigadier Yosua Hutabarat which involved senior police officials, Inspector General Police Ferdy Sambo. The originality of this research lies in its specific focus on an in-depth analysis of the stage of the commodification of content, audience, and workers in the production process of talk show X, with particular emphasis on the murder of Brigadier Yosua Hutabarat